Insulation coordination of quadruple circuit high voltage transmission lines using ATP-EMTP - Dugel, Siti Rugayah (2007)
A significant number of faults in overhead transmission lines are due to lightning strikes which cause back flashovers and hence single or double circuit outages. The continuity and quality of the power supply is therefore can be severely affected by the outages, especially in Malaysia where the isokeraunic level is rather high. The lightning performance of transmission lines is also influenced by the transmission line configuration itself. In Malaysia, the TNB's transmission lines consist of 500 kV or 275 kV double circuits, and 275/132 kV quadruple circuits. It is known that the lower portion of the 132 kV line apparently has the lowest lightning performance.